2017
DOI: 10.17509/ijal.v7i2.8135
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linguistic Influences of Malay Through Cartoons on Indonesian Children’s Language Use in the Home Domain

Abstract: The Malay cartoons that air on Indonesian television channels are now popular among children in Indonesia. The shows Upin & Ipin, Boboboi, and Pada Zaman Dahulu are especially popular with Acehnese children. Initial observations found that these cartoons have played a great role in the increased use of contemporary Malay in their Indonesian. Thus, this study discusses the crosslinguistic influences of Malay from cartoons in Indonesian children's language use in the home domain. Data were collected through reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Akbulut's research (2017) also found that morphological awareness tasks can contribute to vocabulary teaching and can be placed in the Pedagogy and English teaching curriculum. Aziz, Yusuf, Nasir, & Masyithah (2017) in their research, entitled Cross-Linguistic Influences of Malay Through Cartoons on Indonesian Children's Language Use in the Home Domain found a loan or loans, the influence of phonetic, infix, interjection, and intonation in the film of Upin & Ipin, Boboboi, and Pada Zaman Dahulu. In the research, they discussed akak (sister), padan muke, and seronok.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akbulut's research (2017) also found that morphological awareness tasks can contribute to vocabulary teaching and can be placed in the Pedagogy and English teaching curriculum. Aziz, Yusuf, Nasir, & Masyithah (2017) in their research, entitled Cross-Linguistic Influences of Malay Through Cartoons on Indonesian Children's Language Use in the Home Domain found a loan or loans, the influence of phonetic, infix, interjection, and intonation in the film of Upin & Ipin, Boboboi, and Pada Zaman Dahulu. In the research, they discussed akak (sister), padan muke, and seronok.…”
Section: Introductionmentioning
confidence: 99%
“…Also, they discuss interjection ish ish ish and Amboy in Upin and Ipin. The research of Aziz, Yusuf, Nasir, & Masyithah (2017) only examined the problem of the vocabulary of Malay with the Indonesia in General. Their research did not compare the vocabulary of Malay with Banjarese.…”
Section: Introductionmentioning
confidence: 99%
“…As language travels, there is a higher chance that some participants agree that the word 'ummi' in the Arabic language can also be claimed to have a similar meaning, like 'my mother'. Some other Malay influences on the Acehnese and Indonesian languages can be referred to in the work of Aziz et al (2017) and Kanumoyoso (2018).…”
Section: Resultsmentioning
confidence: 99%
“…Kango itself undergoes changes through some Japanese era, in which some become more familiar in the Japanese conversation and some still used in written Japanese (Konno, 2017). Similar to the experience of Indonesia, although it is influenced by various foreign languages, the Malay language (Aziz et al, 2017;Niess, 2016), which is the forerunner of the unifying language, is still used and understood well.…”
Section: Figure 4 Understanding Of Konshugo Suffixed -Tekimentioning
confidence: 93%